Necessary Evils and Interpersonal Sensitivity in Organizations - Molinsky, Andrew; Margolis, Joshua (Academy of Management Review, 2005)
In order to produce a beneficial result, professionals must sometimes cause harm to another human being. To capture this phenomenon, we introduce the construct of “necessary evils ” and explore the inherent challenges such tasks pose for those who must perform them. Whereas previous research has established the importance of treating victims of necessary evils with interpersonal sensitivity, we focus on the challenges performers face when attempting to achieve this prescribed standard in practice.